Development of immunoassays on the Simoa platform to detect and differentiate Tau species at very low concentrations - Martins, Dina Rodrigues (2018)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia